Surveillance of invasive bacterial disease in Alaska, 2005 - National Center for Emerging and Zoonotic Infectious Diseases (U.S.) Division of Division of Preparedness and Emerging Infections Arctic Investigations Program
The Centers for Disease Control and Prevention's Arctic Investigations Program (AIP) in Anchorage, Alaska, maintains a statewide surveillance system for invasive diseases caused by Streptococcus pneumoniae, Haemophilus influenzae, Neisseria meningitidis, and groups A and B streptococci Laboratories throughout the state are requested to send to AIP any isolates of these organisms recovered from a blood culture, CSF, or other normally sterile site Isolate identification is confirmed and, when appropriate, serotyped and tested for antimicrobial susceptibility The objectives of this system are to provide information on disease rates within the state, monitor the emergence of antimicrobial resistance, and to monitor the effectiveness of implemented vaccine programs, such as the 23-valent pneumococcal polysaccharide vaccine, the 7-valent pneumococcal conjugate vaccine and Haemophilus influenzae type b vaccines In 2005, the total numbers of cases of invasive disease caused by these organisms reported to AIP were 122 S pneumoniae, 9 H influenzae, 3 N meningitidis, 36 group A Strep and 24 group B Strep Alaska Native people had higher rates of disease than non-Native people for all surveillance organisms Rates of invasive pneumococcal disease, H influenzae and group A Strep were highest in the YK Delta